Effects of low-dose ionizing radiation on genomic instability in interventional radiology workers - Dominika Kochanova; Sachin Gulati; Matus Durdik; Lukas Jakl; Pavol Kosik; Milan Skorvaga; Katarina Vrobelova; Katarina Vigasova; Eva Markova; Dusan Salat; Andrej Klepanec; Igor Belyaev (Scientific Reports, 2023)
Abstract Interventional radiologists are chronically exposed to low-dose ionizing radiation (IR), which may represent a health risk. The aim of the present study was to evaluate genomic instability by analyzing chromosomal aberrations, micronuclei, and 53BP1 DNA repair foci in peripheral blood lymphocytes of radiologists. Based on the IAEA guidelines on biodosimetry using dicentrics, the average protracted whole-body dose in radiologists were estimated. Since preleukemic fusion genes (PFG) are the primary events leading to leukemia, we also studied their presence by RT-qPCR and FISH. No significant difference in 53BP1 foci and incidence of PFG (MLL-AF4, MLL-AF9, AML1-ETO, BCR-ABL p190) was found in cells of interventional radiologists in comparison to controls. However, our results showed an increased frequency of micronuclei and various types of chromosomal aberrations including dicentrics in interventional radiologists. The average protracted whole body estimated dose was defined at 452.63 mGy. We also found a significantly higher amplification of the MLL gene segment and increased RNA expression in cells of interventional radiologists in comparison to controls. In conclusion, our results showed that long-term low-dose IR induces genomic instability in interventional radiologists.